Unlocking the Caucasus for Empire: Roots, causes and consequences of the Russian annexation of the East Georgian kingdom of Kartli-Kakheti, 1801 - Morkva, Valeriy (Cappadocia Journal of Area Studies, 2021)
The Russian annexation of the Eastern Georgian kingdom of Kartli-Kakheti at the outset of the 19th century ushered in a new stage in the history of the Russian expansion in the Caucasus. The growing Russian influence in the region depended on Russia’s ability to find allies from among the local Caucasian peoples. In this respect the Orthodox Georgians could be counted on by the Tsarist authorities as a potential ally in the area traditionally influenced by the Ottoman Empire and Persia. The control over the Georgian lands lying on the Southern side of the Greater Caucasus ridge was instrumental in allowing the Russians unfettered access across the mountains towards the south. Getting such a foothold as Kartli-Kakheti in the Southern Caucasus would eventually help Russia to gain the upper hand over the mountaineers of the Northern Caucasus as well as to advance its interests in the area between the Black and the Caspian seas. The article analyses the circumstances of the Russian penetration into the Southern Caucasus throughout the 18th century and provides the assessment of the Russian politics towards the Eastern Georgia at the time in question.